RELATIONSHIP BETWEEN FEED CONSUMPTION, BODY WEIGHT GAIN AND FEED CONVERSION OF BROILER CHICKENS GIVEN MORINGA OLEIFERA LEAF FLOUR SUBSTITUTION RATION - Mulyadi; Dedhi Yustendi; Nurhalifah (CV Naskah Aceh, 2026)
This study aims to determine the effect of adding Moringa oleifera leaf flour substitution in broiler rations on broiler chicken growth. The study design used a Completely Randomized Design with four treatments and four replications. The treatments consisted of P0 (100% commercial ration), P1 (97% commercial ration + 3% Moringa leaf flour), P2 (94% commercial ration + 6% Moringa leaf flour), and P3 (91% commercial ration + 9% Moringa leaf flour). The parameters observed included live weight, carcass weight. The data obtained were analyzed using SPSS 27. The results of the Spearman correlation analysis showed that the relationship between feed consumption and body weight gain of broiler chickens had a positive but insignificant correlation (r = 0.389; P>0.05). The relationship between feed consumption and feed conversion also showed a weak and insignificant negative correlation (r = −0.218; P>0.05). In contrast, the relationship between body weight gain and feed conversion showed a very strong and highly significant negative correlation (r = −0.965; P <0.01), indicating that increased body weight gain was followed by a decrease in feed conversion or an increase in feed efficiency. The results of the study concluded that there was a very strong and significant negative relationship between body weight gain and feed conversion in broiler chickens, while the relationship between feed consumption and body weight gain and feed conversion did not show a significant relationship.